Density variations in the Earth's magnetospheric cusps. Issue 3 (15th March 2016) - Walsh, B. M.; Niehof, J.; Collier, M. R.; Welling, D. T.; Sibeck, D. G.; Mozer, F. S.; Fritz, T. A.; Kuntz, K. D.
Abstract: Seven years of measurements from the Polar spacecraft are surveyed to monitor the variations of plasma density within the magnetospheric cusps. The spacecraft's orbital precession from 1998 through 2005 allows for coverage of both the northern and southern cusps from low altitude out to the magnetopause. In the mid‐ and high‐ altitude cusps, plasma density scales well with the solar wind density ( n cusp / n sw ∼0.8). This trend is fairly steady for radial distances greater then 4 R E . At low altitudes ( r < 4 R E ) the density increases with decreasing altitude and even exceeds the solar wind density due to contributions from the ionosphere. The density of high charge state oxygen (O >+2 ) also displays a positive trend with solar wind density within the cusp. A multifluid simulation with the Block‐Adaptive‐Tree Solar Wind Roe‐Type Upwind Scheme MHD model was run to monitor the relative contributions of the ionosphere and solar wind plasma within the cusp. The simulation provides similar results to the statistical measurements from Polar and confirms the presence of ionospheric plasma at low altitudes. Key Points: Cusp electron density scales closely with the solar wind density Ionospheric contributions to the density in the cusp become dominant near four Earth radii Cusp high charge state oxygen density scales with solar wind density